2020
DOI: 10.1371/journal.pone.0236635
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between plant-eating and hair evacuation in snow leopards (Panthera uncia)

Abstract: Although most felids have an exclusive carnivore diet, the presence of plant matter in scat has been reported among various species. This indicates that there may be an adaptive significance to the conservation of plant-eating behavior in felid evolution. Some studies have hypothesized that felids consume plants for self-medication or as a source of nutrition. In addition, it is thought that plant intake helps them to excrete hairballs, however, no scientific work has confirmed these effects. Thus, the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Sugar cane‐derived fibers reduced the size of hairballs in the scat of domestic cats (Loureiro et al., 2014 ). However, cellulose, one of the main insoluble fibers, did not have such an effect (Loureiro et al., 2014 ), and plant intake had little effect on hair evacuation in captive snow leopards (Yoshimura et al., 2020 ). Owing to the aforementioned attributes of prey items, smaller carnivores are considered to be more tolerant to indigestible food items (Jethva & Jhala, 2004 ; Rühe et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sugar cane‐derived fibers reduced the size of hairballs in the scat of domestic cats (Loureiro et al., 2014 ). However, cellulose, one of the main insoluble fibers, did not have such an effect (Loureiro et al., 2014 ), and plant intake had little effect on hair evacuation in captive snow leopards (Yoshimura et al., 2020 ). Owing to the aforementioned attributes of prey items, smaller carnivores are considered to be more tolerant to indigestible food items (Jethva & Jhala, 2004 ; Rühe et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hoppe‐Dominik stated that leopards ( Panthera pardus ) may eat grasses to keep their digestive tract moving during starvation (Hoppe‐Dominik, 1988 ). However, captive snow leopards also ate plants regularly even though they were fed daily (Yoshimura et al., 2020 ), suggesting that starvation is not always the trigger for plant eating. Furthermore, it has been suggested that grasses are selectively eaten because they are free of secondary plant compounds, unlike those in other plant groups (Hoppe‐Dominik, 1988 ).…”
Section: Domestic Cat Lineagementioning
confidence: 99%
See 3 more Smart Citations